Temperature-dependent photoluminescence and energy-transfer dynamics in Mn2+-doped (C4H9NH3)(2)PbBr4 two-dimensional (2D) layered perovskite - Bakthavatsalam, Rangarajan; Biswas, Anupam; Chakali, Madhu; Bangal, Prakriti Ranjan; Kore, Bhushan P.; Kundu, Janardan (Journal of Physical Chemistry C, 2019)
Reported here are the low-temperature photoluminescence (PL), energy-transfer mechanism, and exciton dynamics of Mn2+-doped two-dimensional (2D) perovskites that show interesting differences from their three-dimensionally doped counterpart. Dopant emission in 2D system shows increased PL intensity and shortened lifetime with increase of temperature and strong dopant emission even at low temperatures. Transient absorption (TA) spectroscopy reveals the dominant role of ``hot'' excitons in dictating the fast energy-transfer timescale. The operative dynamics of the generated hot excitons include filling up of existing trap states (shallow and deep) and energy-transfer channel from hot excitons to dopant states. Global analysis and target modeling of TA data provide an estimate of excitons (hot and band edge) to a dopant energy-transfer timescale of similar to 330 ps, which is much faster than the band edge exciton lifetime (similar to 2 ns). Such fast energy-transfer timescale arises due to enhanced carrier exchange interaction resulting from higher exciton confinement, increased covalency, and involvement of hot excitons in the 2D perovskites. In stark contrast to three-dimensional systems, the high energy-transfer rate in 2D system results in high dopant emission intensity even at low temperatures. Increased intrinsic vibronic coupling at higher temperatures further supports efficient Mn2+ sensitization that ultimately dictates the observed temperature dependence of the dopant emission (intensity, lifetime).